Equilibrium treatment of spin-depolarizing modes in mass asymmetric heavy-ion systems - Schmitt, R. P.; Pacheco, A. J. (North Holland Publishin Co., 1982)
Fil: Schmitt, R.P. Department o f Chemistry and Cyclotron Institute, Texas Á & M University; Estados Unidos